Pengaruh Harga, Kemudahan Penggunaan Dan Promosi Terhadap Keputusan Pembelian Dalam Memilih Grabfood (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2019) - Ainur Ropik; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to find out and analyze the relationship between Price, Ease of Use and Promotion on Purchase Decisions in Choosing Grabfood. This research uses studies on students of the Faculty of Economics & Business, Islamic University of Malang, class of 2019. The data was obtained by distributing questionnaires to students of the Faculty of Economics & Business, Islamic University of Malang, class of 2019, who were selected by purposive sampling. Determining the number of samples using the slovin formula and the results obtained were 90 respondents. The analytical method used in this study is multiple linear regression analysis, using SPSS 16. The results of this study indicate that price, ease of use and promotion simultaneously influence purchasing decisions. Partially Price has an effect on purchasing decisions, Ease of Use partially influences purchasing decisions, Promotions partially has no effect on Purchasing decisions. Keywords: Price, Ease of Use, Promotion, Purchase Decision